Non-equilibrium radiation modeling in a gas kinetic simulation code. (April 2022) - Beyer, Julian; Pfeiffer, Marcel; Fasoulas, Stefanos
Highlights: First steps toward the coupling of a particle solver with a radiation module. Line-by-line radiation modeling to determine non-equilibrium emission and absorption. Photon Monte Carlo radiative energy transfer modeling. Adaptations to address downsides of a Monte Carlo solver for radiative energy transfer. Parallelization concept for highly parallel simulations. Abstract: Radiation modeling is implemented in the highly parallel gas kinetic, open-source plasma simulation suite PICLas. A photon Monte Carlo approach for three-dimensional radiative energy transfer is developed. Since these kind of solvers have the disadvantage of high computational costs and statistical fluctuations, these points are addressed by specific adaptations to the solver. An approach to simulate axisymmetric problems is presented as well as noise reducing methods. Results are compared to a semi-infinite black body radiating cylinder, where an analytical solution is known, and a good agreement for both, three-dimensional and axisymmetric simulations is demonstrated. It is also shown that the implemented noise reducing methods can reduce statistical fluctuations. To calculate radiative properties in terms of emission and absorption coefficients, a line-by-line method is implemented and compared with good agreement to results obtained with other well-established radiation codes. The FIRE II reentry is used as a test case for a simulation combined with DSMC. Unidirectional coupling with the developed radiation modules shows good results compared to measured values as well as in performance scaling.